1996
DOI: 10.1523/jneurosci.16-20-06433.1996
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor and Neurotrophin-3 Differentially Regulate the Proliferation and Survival of Developing Rat Brain Oligodendrocytes

Abstract: There is increasing evidence that the neurotrophins, particularly nerve growth factor (NGF) and neurotrophin-3 (NT-3), play a role in the regulation of glial development in the CNS. Recent studies have shown that the proliferation of optic nerve-derived O2A progenitors (OLPs) is potentiated by NT-3 in combination with platelet-derived growth factor, whereas NT-3 alone supports the survival of their differentiated progeny (Barres et al., 1994). In this study, we have examined the expression of the high-affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
184
1
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(202 citation statements)
references
References 71 publications
15
184
1
2
Order By: Relevance
“…This concept of a critical level of ERK activation has already been noted in the induction of O2A proliferation. As was mentioned above, increases in O2A proliferation were noted only after a high enough level of ERK activity was reached (Cohen et al, 1996). While these results indicate a potential contradiction in the signalling pathways between primary OL and CG-4, they do not necessarily negate the use of CG-4 as an OL model.…”
Section: Mature Olmentioning
confidence: 54%
“…This concept of a critical level of ERK activation has already been noted in the induction of O2A proliferation. As was mentioned above, increases in O2A proliferation were noted only after a high enough level of ERK activity was reached (Cohen et al, 1996). While these results indicate a potential contradiction in the signalling pathways between primary OL and CG-4, they do not necessarily negate the use of CG-4 as an OL model.…”
Section: Mature Olmentioning
confidence: 54%
“…Activation of TrkA in OLGs negates the cell death mediated by p75 (65), suggesting that the expression levels of TrkA and p75 determine the rodent OLG response to NGF. TrkA expression has been demonstrated in mature OLGs (66,67), and NGF enhances the survival of differentiated OLGs (67). Since we also confirmed the expression of both TrkA and p75 in OLGs, it is likely that NGF can enhance OLG survival in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in PC12 cells treated with antisense oligonucleotides to downregulate TrkA expression, BDNF but not NGF can rescue from serum-withdrawal (Taglialatela et al, 1996). A very likely explanation for the effect of distinct neurotrophins in the oligodendrocyte system is the presence of TrkB and TrkC receptors in these cells (Cohen et al, 1996). An alternative explanation, in cells not expressing other Trk receptors, is the differential ability of neurotrophins to activate distinct signal transduction pathways.…”
Section: P75 As a Ligand-dependent Cell Death Moleculementioning
confidence: 99%
“…Similarly, downregulation of p75, using antisense oligonucleotides, results in either decreased or increased survival depending on the developmental stage of DRG neurons (Barrett and Bartlett, 1994). The apoptotic role of p75 has been observed primarily in terminally differentiated cells, while contrasting effects have been observed in undifferentiated cells, such as oligodendrocyte progenitors, medulloblastomas, and tumor cell lines (Cohen et al, 1996;Cortazzo et al, 1996;Muragaki et al, 1997). Although it remains to be demonstrated that p75 signaling affects cell cycle genes, this is an attractive hypothesis that may potentially explain the paradox of p75 being a survival molecule in cultured neuroblastomas (Cortazzo et al, 1996) and apoptotic in primary cultures of post-mitotic cells.…”
Section: Requirements For An Apoptotic Signalmentioning
confidence: 99%